Retinal Distribution and Extracellular Activity of Granzyme B: A Serine Protease That Degrades Retinal Pigment Epithelial Tight Junctions and Extracellular Matrix Proteins - Matsubara, Joanne A.; Tian, Yuan; Cui, Jing Z.; Zeglinski, Matthew R.; Hiroyasu, Sho; Turner, Christopher T.; Granville, David J. (Frontiers in Immunology, 2020)
Granzymes are a family of serine proteases first shown to be intracellular initiators of immune-mediated cell death in target pathogenic cells. In addition to its intracellular role, Granzyme B (GzmB) has important extracellular functions in immune regulation and extracellular matrix (ECM) degradation. Verified substrates of extracellular GzmB activity include tight junctional and ECM proteins. Interestingly, little is known about the activity of GzmB in the outer human retina, a tissue in which the degradation of the tight junctional contacts of retinal pigment epithelial (RPE) cells and within the external limiting membrane, as well as remodelling of the ECM in Bruch’s membrane, cause the breakdown of the blood-retinal barrier and slowing of metabolite transport between neuroretina and choroidal blood supply. Such pathological changes in outer retina signal early events in the development of age-related macular degeneration (AMD), a multifactorial, chronic inflammatory eye disease. This study is the first to focus on the distribution of GzmB in the outer retina of the healthy and diseased post-mortem human eye. Our results revealed that GzmB is present in RPE and choroidal mast cells. More immunoreactive cells are present in older (> 65 yrs) compared to younger (<55 yrs) donor eyes, and choroidal immunoreactive cells are more numerous in eyes with choroidal neovascularization (CNV), while RPE immunoreactive cells are more numerous in eyes with soft drusen, an early AMD event. In vitro studies demonstrated that RPE-derived tight junctional and ECM proteins are cleaved by exogenous GzmB stimulation. These results suggest that the increased presence of GzmB immunoreactive cells in outer retina of older (healthy) eyes as well as in diseased eyes with CNV (from AMD) and eyes with soft drusen exacerbate ECM remodelling in the Bruch’s membrane and degradation of the blood-retinal barrier. Currently there are no treatments that prevent remodelling of the Bruch’s membrane and/or the loss of function of the outer blood-retinal barrier, known to promote early AMD changes, such as drusen deposition, RPE dysfunction and pro-inflammation. Specific inhibitors of GzmB, already in preclinical studies for non-ocular diseases, may provide new strategies to stop these early events associated with the development of AMD.